Chemical constituents of Odontites serotina (Lam.) Dumort. (Orobanchaceae). (June 2020) - Wang, Cong-Cong; Zang, Er-Huan; Zhang, Chun-Hong; Bo, Agula; Gong, Xue; Li, Min-Hui
Abstract: The study of the whole plants of Odontites serotina (Lam.) Dumort. has led to the isolation of one nucleoside compound (2 ), three iridoids (1, 3, and 4 ), two phenylethanolic glycosides (6 and 8 ), four phenolic acids (5, 10, 12, and 15 ), and nine flavonoids (7, 9, 11, 13, 14, and 16 –19 ). The structures of the compounds were identified by nuclear magnetic resonance (NMR) and high-resolution mass spectrometer. To the best of our knowledge, this is the first study to describe the isolation and identification of compounds 2 –3, 6 –8, 10, 12, 14 –16, and 19 in O. serotina. The chemotaxonomic significance of these compounds was discussed. Graphical abstract: Image 1 Highlights: In our research, eleven compounds were isolated from Odontites serotina for the first time. The chemical data provided the basis for the relationship between Odontites, Cymbaria, Bellardia, and Parentucellia. Our data confirms the correctness of the reclassification of the genus Odontites from Scrophulariaceae into Orobanchaceae, and have important chemotaxonomic significance.